(untitled) (Pulse, 2014)
Back ground: Recent advances in psychological, medical, and physiological research have led to a new way of thinking about health and illness. This conceptualization, which has been labeled the biopsychosocial model, views health and illness as the product of a combination of factors including biological characteristics (e.g., genetic predisposition), behavioral factors (e.g., lifestyle, stress, health beliefs), and social conditions (e.g., cultural influences, family relationships, social support).Objectives: Create awareness about psychological support, understanding behavioral and contextual factors, preventing illness. DOI: http://dx.doi.org/10.3329/pulse.v6i1-2.20347 Pulse Vol.6 January-December 2013 p.37-40